Cover Image - Jianbo Yuan; Yang Yu; Xiaojun Zhang; Shihao Li; Jianhai Xiang; Fuhua Li (Reviews in Aquaculture, 2023)
The cover image is based on the Review Article Recent advances in crustacean genomics and their potential application in aquaculture by Jianbo Yuan et al., https://doi.org/10.1111/raq.12791 . image